Understanding the New Analogue Photography: Meanings, Methodologies and Aesthetics - Margadona, Laís Akemi (New Explorations)

(untitled) (New Explorations Association, 2023)
This paper examines the resistance and revival of outmoded photographic technologies, in a new format we call “new analogue photography”. This type of image resignifies old analogue practices as stated by Ansel Adams (2019a, 2019b, 2018) in three key areas: 1. meaning, 2. methodology, and 3. aesthetics. It is the grain image adapted to the connected media ecosystem in post-photographic times. The contribution of millennials and gen Z to the growth of this type of photography is presented and discussed. At the conclusion, the decalogue of the new analogue photography is stated, summing up its practice and significance across ten topics.